1973
DOI: 10.1111/j.1469-8137.1973.tb02019.x
|View full text |Cite
|
Sign up to set email alerts
|

SULPHUR DIOXIDE: ITS EFFECT ON PHOTO‐SYNTHETIC 14C FIXATION IN LICHENS AND SUGGESTED MECHANISMS OF PHYTOTOXICITY

Abstract: Summary The toxicity to lichens of dissolved sulphur dioxide (as measured by net photosynthetic 14C fixation) was studied as a function of pH and is linked with the oxidation‐reduction properties of sulphur dioxide. An examination of pigments from lichens and spinach exposed to aqueous sulphur dioxide in vivo and in vitro suggests that the increased toxicity observed at low pH values is associated in part with the destruction of chlorophyll by an irreversible oxidation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(61 citation statements)
references
References 25 publications
5
51
0
1
Order By: Relevance
“…The biological correlation between the effects of aqueous and gaseous exposures established by Saunders (1966) on the basis of the work with Diplocarpon rosae Wolf spores is often referred to in lichen and other plant injury studies (Puckett et al, 1973;Hocking and Hocking, 1977;Tanaka, Takanashi and Yatazawa, 1974). Aqueous levels by this biological scale are considered to be a thousandfold less effective than gaseous concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The biological correlation between the effects of aqueous and gaseous exposures established by Saunders (1966) on the basis of the work with Diplocarpon rosae Wolf spores is often referred to in lichen and other plant injury studies (Puckett et al, 1973;Hocking and Hocking, 1977;Tanaka, Takanashi and Yatazawa, 1974). Aqueous levels by this biological scale are considered to be a thousandfold less effective than gaseous concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Several vv'orkers have used different concentrations of dissolved SOj in liquid or semi-liquids whilst manipulating the different solubility products of SO, through alteration of pH (Puckett et al, 1973;Babich & Stotzky, 1980). In the experiment of , differential inhibition was concluded to be a selective effect of SO'^ on microorganisms, but the effective concentration of SOg in the presence of media containing carbohydrates was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these phenomena, the dry deposition of SO.^ and the enhancement of NP activity on SO.ê xposure of hydrated lichen thalli, have previously been reported in separate experiments. Winner et al (1978) documented the sorption of gaseous SO.^ on desiccated lichen thalli, using sulphur isotopes to trace deposition patterns, while Puckett et al, (1973) observed enhanced rates of NP following exposure of hydrated thalli to SO.^ concentrations of 0-75 //I T'. Similarly Beekley & Hofiman (1981) found that short-term exposure of (hydrated) Parmelia bolliana thalli to SO2 concentrations of 001 //I L' enhanced rates of NP uptake by up to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that although photosyntbetic rates were significantly enhanced in lichen samples they placed within the treatn-ient area, local populations were almost non-existent within this zone. Thus, while low level SOg exposure clearly results in short term stimulation of photosynthetic activity, underlying physiological responses, variously suggested to include the action of sulphite and bisulphite ions as reducing agents and uncoupling of electron transport from photophosphorylation (Puckett et al, 1973;Sheridan, Sanderson & Kerr, 1976), may ultimately prove detrimental to lichen populations.…”
Section: Discussionmentioning
confidence: 99%